Salicylic acid confers cadmium tolerance in wheat by regulating photosynthesis, yield and ionic homeostasis - Umer Hayat; Kaleem ul din; Muhammad Ahmad; Usman Zulfiqar; Maryium Sajjad; Muhammad Faisal Maqsood; Walid Soufan; P. V. Vara Prasad; Ivica Djalovic (Scientific Reports)
Abstract Wheat (Triticum aestivum L.) productivity and quality can be threatened by soil cadmium (Cd) contamination, posing a concern to food security. Salicylic acid (SA) is an endogenously produced signaling molecule that activates the defense system imparting abiotic stress tolerance in plants. Hence, an experiment was conducted to explore the roles of foliar application of SA in ameliorating Cd toxicity in two wheat varieties. The treatments comprised of, a) Cd stress: i) Cd0 = control (No Cd), Cd1 = 500 µM Cd stress at 30 days after sowing (DAS); SA applications: (i) SA0 = control (No SA) (ii) SA1 = 0.5 mM SA at 32 DAS, and c) Wheat varieties: (i) Anaj-17 and (ii) Akbar-19. The experiment was carried out with three replicates in a completely randomized design (CRD). The findings of the study have revealed that Cd stress prominently reduced the plant growth and yield, gaseous exchange attributes, and relative water content of both wheat varieties, and more reduction was observed in Anaj-17 as compared to Akbar-19. Plant height, economic yield, photosynthetic rate, and relative water content were decreased by (9.80 and 8.20%), (12.2 and 6.58%), (20 and 11.32%), and (12.5 and 10%) in Anaj-17 and Akbar-19 respectively. Further, SPAD value and chlorophyll fluorescence decreased under Cd toxicity in both wheat cultivars as compared to non-stress conditions. Contrarily, electrolyte leakage and Cd contents were increased in the plants as compared to the control. However, the foliar applications of SA in Cd-stressed plants significantly improved the plant growth and yield attributes, relative water content, gas exchange attributes, and chlorophyll content in both wheat varieties as compared to control-no SA applied. In addition, chlorophyll fluorescence and nutrient uptake were also improved under SA applications as compared to control. However, SA played an ameliorative role in reducing Cd-toxicity by reducing the electrolyte leakage and Cd uptake by the plants. Among the varieties, Akbar-19 outperformed the Anaj-17 to impart Cd toxicity under SA applications based on plant morphophysiological attributes. Hence, the outcomes of the experiment recommended that the foliar treatment of SA amended the Cd tolerance of wheat varieties by improving plant physiological and biochemical attributes.